Private Enforcement and Market Regulation - Sara Landini (Market and Competition Law Review)
The article examines the technique of private enforcement as a juridical instrument to protect the market in combination with the punitive sanction mechanisms of public law. After a first definition of private enforcement, we investigate the position taken by the European Commission on the use of private enforcement, verifying its function with respect to the objectives of market protection. The main instruments of private enforcement are therefore considered: civil liability, termination of the contract, nullity of the contract, injunction. We will focus on the main constraints to the application of the abovementioned instruments of private enforcement proposing solutions in the light of an overcoming of the boundaries between public law and private law. As highlighted in Directive 2014/104/EU, “the practical effect of the prohibitions laid down requires that anyone – be they an individual, including consumers and undertakings, or a public authority – can claim compensation before national courts for the harm caused to them by an infringement of those provisions.” For this reason it is important to consider all the different private enforcement tools and try to remove the obstacles to their effective functioning. Private law is activated on the action of individuals who exercise the rights recognised by the law. Individuals being closer to the emergence of the problem are able to represent the violation of the interests at stake according to the logic proper to the principle of subsidiarity. The Principle of subsidiarity states that a wider and greater body, such as a government, should not exercise functions that can be carried out efficiently by a smaller one, such as an individual or a private group, acting independently.